Decarbonizing K-12 Schools in the United States: Challenges, Opportunities and Future Directions - Ryan Kmetz; Gus Norrbom (Journal of Education in Science, Environment and Health)
K-12 schools in the United States significantly contribute to greenhouse gas emissions due to aging infrastructure, inefficient energy practices, and a heavy reliance on fossil fuels. Addressing these issues through decarbonization is not just important—it is becoming a critical initiative aimed at reducing environmental impact while simultaneously improving the educational environments we offer our students. This paper examines the current landscape of decarbonization efforts in K-12 schools, focusing on our challenges, opportunities, and emerging best practices. By analyzing existing strategies and policies at the federal, state, and local levels, this paper highlights how these efforts are supported—or, in some cases, hindered—by the frameworks in place. The benefits of decarbonization are clear: improved indoor air quality, enhanced learning conditions, and reduced operational costs, all of which contribute to a healthier and more effective educational environment. This research also delves into successful case studies, showcasing innovative approaches and replicable models in other schools nationwide